1995
DOI: 10.1002/ca.980080111
|View full text |Cite
|
Sign up to set email alerts
|

The use of multiple‐choice tests in anatomy: Common pitfalls and how to avoid them

Abstract: Multiple-choice questions (MCQ) are widely used to evaluate students in the health sciences, including anatomy. Unusual responses in 90 simple MCQ examinations have been identified and classified as to cause, including a number of illustrated examples. About one-quarter of these errors were attributable to the teacher and could have been avoided by a critical analysis of the questions before use. The increasing use of sophisticated formats of the MCQ in medical education indicates that teachers need to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…MCQs have many merits and can produce meaningful assessment of knowledge, though their validity can suffer for many reasons (Vahalia et al, ; Downing, ). Severo et al () found a significant effect on the calculation of student marks when a formula scoring method instead of a number scoring method was used.…”
Section: Discussionmentioning
confidence: 99%
“…MCQs have many merits and can produce meaningful assessment of knowledge, though their validity can suffer for many reasons (Vahalia et al, ; Downing, ). Severo et al () found a significant effect on the calculation of student marks when a formula scoring method instead of a number scoring method was used.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the use of practical and oral examinations was widespread but nowadays written assessment methods are more commonly used and the use of computers is growing (Vahalia et al, 1995;Rowland et al, 2011). Examples of written methods include single best answer questions, extended matching questions, short answer questions, and essay questions.…”
Section: Assessment In Medical Education and Anatomymentioning
confidence: 99%
“…Multiple Choice Questions (MCQs) are widely used in assessment across many disciplines in HE because they can efficiently test a broad range of cognitive knowledge, particularly in large classes (Hays, 2008;McCoubrie, 2007;Tarrant, Ware, & Mohammed, 2009). However, MCQs are sometimes poorly written, and in such cases, they assess recall of knowledge rather than higher-order thinking (Vahalia, Subramaniam, Marks & De Souza, 1995). Such poor quality items can have detrimental effects on learning (Downing, 2005).…”
Section: Introductionmentioning
confidence: 99%